In-Depth Review For Evaluating Power Usage of Solar Cells Over Their Entire Lifespan - Rawdhan, Alaa; Ahmed, Mohammed (Anbar Journal of Engineering Sciences, 2024)
Solar cells play a vital role in renewable energy systems, and ongoing research is dedicated to enhancing their power efficiency and longevity. Advancements in perovskite solar cells, particularly in power conversion efficiency (PCE), have shown significant progress, confirming its viability as a technology. Perovskite solar cells have achieved power conversion efficiency (PCE) levels of up to 25.5%, comparable to conventional photovoltaic technologies like silicon, gallium arsenide, and cadmium telluride. The substantial enhancement in power conversion efficiency figures over the last decade has shown a remarkable advancement in the efficiency of perovskite solar cells. This study examines the trajectory of perovskite solar cells in becoming economically feasible and generally embraced as a critical renewable energy technology. The advancement of flexible and wearable solar cells, together with miniature solar-powered sensors, has increased the efficiency of solar cell power production. Perovskite solar cells have shown a specific power of 23 W/g, much higher than traditional silicon or gallium arsenide solar cells. Further research is needed to address the challenges related to perovskite solar cells’ stability and power conversion efficiency. Perovskite solar cells integrated with energy storage units have the potential to enhance the overall efficiency of the system. This study discusses an approach to improve the efficiency of novel solar cells, specifically focusing on lead-free tin-based perovskite solar cells and tandem solar cells. The advancement of technology in thin films, such as hybrid nanocomposite thin films and quantum dot-sensitive solar cells, has the potential to improve the efficiency of solar cells. The primary outcome of this study is derived from the following inference: incorporating plasmatic nanostructures into thermal energy systems will enhance their efficiency and sustainability by integrating solar energy.